Antioxidant and antibacterial extracts from rambutan (Nephelium lappaceum) skins: Exploring the Potential of Transforming Agricultural Byproducts into Functional Supplements - Álvarez-Valverde, Victor (2024)
Rambutan (Nephelium lappaceum L.) is a tropical fruit characterized by its oval shape and hairy skin, primarily valued for its juicy pulp. The peels, constituting 45% of the fruit’s weight, are a source of valuable compounds like geraniin, ellagic acid, and quercetin. These peels possess antimicrobial properties effective against various bacteria, making them suitable for food preservation and packaging. Additionally, rambutan extracts hold promise as supplements in animal feed, enhancing growth and reducing methane production. This research delves into the antioxidant and antimicrobial attributes of diverse rambutan varieties. The skin (exocarp) of rambutan fruits from three Costa Rican cultivars -Creole, Rongrein, and Yellow- were collected and processed. Total polyphenolic content (TPC), proanthocyanidins, antioxidant activity, geraniin content, and antimicrobial activity were determined for the three varieties. Also, proanthocyanidin-enriched fractions from rambutan extracts were generated and analyzed. The results revealed TPC and antioxidant activity variations among different rambutan varieties and harvest years. All rambutan extracts displayed antimicrobial activity. In conclusion, the research underscores the rich antioxidant content in rambutan peels, irrespective of the variety, and underscores their potential for use in both human and animal nutrition due to their chemical composition.